2004
DOI: 10.1007/s10342-004-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term nutritional trends of conifer stands in Europe: results from the RECOGNITION project

Abstract: Since 1999Since -2002 the European Commission has funded and the European Forest Institute has coordinated the interdisciplinary RECOGNITION project aiming at elucidating the causes of the growth acceleration which has been observed in some forest tree species in several parts of Europe. Within this project, it was our task to identify and quantify long-term changes in the nutritional status of representative forest stands that potentially could explain this growth increase, using available long-term series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 33 publications
3
49
1
3
Order By: Relevance
“…Increased N deposition during the last decades (Galloway 2001) balanced out the growth limitation by N in many temperate forests (Nihlgård 1985), which eventually became N saturated (Aber et al 1998). The improved N nutrition initially led to increased forest growth (Braun et al 1999;Högberg et al 2006;Spiecker 1999), but might also have provoked nutrient imbalances (Aber et al 1998) including P deficiency (Flückiger and Braun 1998;Mellert et al 2004;Mohren et al 1986). In N-saturated forests, a shift from N to P limitation of forest growth has already been observed (Braun et al 2010;Gradowski and Thomas 2006;Peñuelas et al 2013) and may be due to several processes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased N deposition during the last decades (Galloway 2001) balanced out the growth limitation by N in many temperate forests (Nihlgård 1985), which eventually became N saturated (Aber et al 1998). The improved N nutrition initially led to increased forest growth (Braun et al 1999;Högberg et al 2006;Spiecker 1999), but might also have provoked nutrient imbalances (Aber et al 1998) including P deficiency (Flückiger and Braun 1998;Mellert et al 2004;Mohren et al 1986). In N-saturated forests, a shift from N to P limitation of forest growth has already been observed (Braun et al 2010;Gradowski and Thomas 2006;Peñuelas et al 2013) and may be due to several processes.…”
Section: Discussionmentioning
confidence: 99%
“…fuel combustion, intensive agriculture) may induce or aggravate nutritional imbalances in nutrient-poor forest ecosystems. Although tree nutrient demand augments with increased forest productivity resulting from the fertilizer effect of N deposition (Mellert et al, 2004) and from certain changes in sylvicultural practices and in climate conditions (Lebourgeois et al, 2001), the supply of P and base cations remains generally low in forest soils and is likely to decrease with soil acidification (Adams, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, such data sets were scarce and were obtained, for example, by using the control plots of fertilization or thinning trials (Mellert et al, 2004). Another option consisted in re-sampling stands after a certain time lag (Alfani et al, 2000;Duquesnay et al, 2000); however, this method did not allow researchers to separate the long-term trends from the inter-annual variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regularly fertilized forests, under the controlled conditions, the positive influence of fertilization on tree growth was observed (Moller 1992;Fox et al 2007). Mellert et al (2004) observed that improvements in N nutrition were reflected in positive trends in foliar N concentration and constant or increased needle mass (100-needle weight) or a positive trend in the foliar N content (product of foliar N concentration and needle mass). Our study revealed that after the nutrient concentration increased, a growth decline was observed.…”
Section: Discussion Fertilization Alters Tree Growthmentioning
confidence: 99%